Pengaruh Kecerdasan Emosional dan Stres Kerja Terhadap Burnout pada Karyawan Manufaktur di Kabupaten Karawang - Dimas Prabowo; Cempaka Putrie Dimala; Ananda Saadatul Maulidia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This This research aims to examine the influence of emotional intelligence and work stress on burnout in manufacturing employees in Karawang district. Participants in this research were employees of manufacturing companies in Karawang district and domiciled in Karawang district with a total of 383 participants. The method used is quantitative with a causality design and accidental sampling technique. Data was collected using psychological scales including the Emotional Intelligence Questionnaire (EIQ) scale from Goleman (2009) to measure emotional intelligence, the Job Stress Scale (JSS) which was prepared referring to the theory of Parker dan DeCotiis (1983) to measure the work stress scale and the Oldenburg burnout scale. inventory (OLBI) to measure burnout tendencies. Data analysis used in this research is normality test, linearity test, multiple regression test and coefficient of determination with the help of the SPSS program. Based on the results of research that has been conducted, there is an influence of emotional intelligence and work stress on burnout with a significance value of 0.000. The results of the coefficient of determination test show that emotional intelligence and work stress on burnout have an influence of 28.8%. Further research is recommended to focus on more specific and contextual intervention strategies according to the needs of manufacturing employees in Karawang district.